Estimating the Causal Relationship between Farmer Exchange Rate, Food Consumer Price Index and Inflation: ARDL Bounds and Toda-Yamamoto Approaches - Wahyuni, Andi Sri; Alwago, Wycliffe Obwori (Universitas Muhammadiyah Surakarta, 2023)
The aim of this study is to investigate the causality between the exchange rate for farmers, the consumer price index for food, and inflation in five major cities in South Sulawesi, Indonesia. The Autoregressive Distributed Lag (ARDL) bounds testing and Toda-Yamamoto causality procedures are employed for analyzing monthly data from January 2015 to July 2022, allowing for the examination of both short-term and long-term effects. The empirical findings indicate a long-run equilibrium between the variables. The results reveal that in both the short run and long run, a 1% change in food prices results in approximately a 100% increase in the farmers' exchange rate. However, the Toda-Yamamoto causality test reveals that, except for a unidirectional causality relationship from the farmers' exchange rate to inflation in the food consumer price index, there is no significant causal relationship between the variables in the studied period and cities. This research contributes new insights into the interplay between inflation and the exchange rate for farmers, particularly in regions where agriculture is the primary source of income.